Examination of the toxicity of a new group of Karenia papilionacea isolated from the Yellow Sea, China, to multiple species of marine aquatic animals - Chen, Qiantong; Gao, Menghan; Zhang, Ning; Li, Lang; Fan, Yingyi; Zhao, Jiali; Xu, Xintong; Tao, Zhe; Deng, Yunyan; Zhang, Yulei; Li, Feng; Lin, Siheng; et al. (Frontiers in Microbiology, 2025)
IntroductionThe dinoflagellate genus Karenia G. Hansen and Moestrup is notorious for forming harmful algal blooms (HABs), most of which can produce a variety of potent toxins (e.g., brevetoxins), killing fish and other aquatic animals above a certain cell density. Among the 11 currently accepted Karenia species, more than half of which are toxic, 8 species (K. bicuneiformis, K. brevis, K. brevisulcata, K. hui, K. longicanalis, K. mikimotoi, K. papilionacea, and K. selliformis) have been reported or described in Chinese coastal waters. Among these, K. papilionacea is globally distributed, with records in Asia, Europe, America, and Oceania. In China, it occurs in the East and South China Seas, though its morphological characterization and toxicology have not been well documented.MethodsIn this study, we established a clonal culture of Karenia papilionacea through single-cell isolation from the coast of Qingdao (belonging to the Yellow Sea), China, and characterized its morphology using light microscopy (LM) and scanning electron microscopy (SEM), as well as its phylogeny based on large subunit (LSU) rDNA sequences. More importantly, we characterized the impact of K. papilionacea culture on brine shrimp egg hatching, as well as its toxicity to marine animals (rotifers, brine shrimp, and finfish) using laboratory bioassays.ResultsWe observed the typical diagnostic features of K. papilionacea. In phylogenetic trees inferred using Bayesian inference (BI) and maximum likelihood (ML) techniques, the Yellow Sea strain branched together with other entities of K. papilionacea, but formed a new group, which is different from other strains reported in the East and South China Seas. The genetic distances among our strain of K. papilionacea and other isolates ranged from 0.002 to 0.011, corresponding to 6–23 base differences. The Yellow Sea strain exhibited significant lethal effects on rotifer, brine shrimp, and finfish, but had a minor impact on the hatching success of brine shrimp eggs.DiscussionThis study reports K. papilionacea in northern China for the first time, expanding the known distribution range of this toxic HAB-forming species along the Chinese coast. Our findings establish a foundation for monitoring and risk assessment of K. papilionacea in Chinese coastal waters and advance fundamental ecological knowledge of this toxic species. Future studies are needed to characterize toxins produced by geographical strains of K. papilionacea.